Circulating Memory B Cells in Early Multiple Sclerosis Exhibit Increased IgA+ Cells, Globally Decreased BAFF-R Expression and an EBV-Related IgM+ Cell Signature - Leffler, Jonatan; Trend, Stephanie; Ward, Natalie C.; Grau, Georges E.; Hawke, Simon; Byrne, Scott N.; Kermode, Allan G.; French, Martyn A.; Hart, Prue H. (Frontiers in Immunology, 2022)
Multiple sclerosis (MS) is an immune-mediated inflammatory disease of the central nervous system that results in demyelination of axons, reduced signal transmission and muscular mobility. Recent findings suggest that B cells play a significant role in disease development and pathology. To further explore this, B cell profiles in peripheral blood from 28 treatment-naive patients with early MS were assessed using flow cytometry and compared to 17 healthy controls. Conventional and algorithm-based analysis revealed a significant increase in MS patients of IgA+ memory B cells (MBC) including CD27+, CD27- and Tbet+ subsets. Screening circulating B cells for markers associated with B cell function revealed a significantly decreased expression of the B cell activation factor receptor (BAFF-R) in MS patients compared to controls. In healthy controls, BAFF-R expression was inversely associated with abundance of differentiated MBC but this was not observed in MS. Instead in MS patients, decreased BAFF-R expression correlated with increased production of proinflammatory TNF following B cell stimulation. Finally, we demonstrated that reactivation of Epstein Barr Virus (EBV) in MS patients was associated with several phenotypic changes amongst MBCs, particularly increased expression of HLA-DR molecules and markers of a T-bet+ differentiation pathway in IgM+ MBCs. Together, these data suggest that the B cell compartment is dysregulated in MS regarding aberrant MBC homeostasis, driven by reduced BAFF-R expression and EBV reactivation. This study adds further insights into the contribution of B cells to the pathological mechanisms of MS, as well as the complex role of BAFF/BAFF-R signalling in MS.